Proceso de tratamiento por electrocoagulación y radiación solar visible de una solución acuosa modelo del colorante textil disperso “taicron-red”: Treatment process by electrocoagulation and visible solar radiation of an aqueous solution model of the dispersed textile dye "taicron-red" - Concepción Gamarra, Lia Elis (2024)
The textile industry, one of the fastest growing industries, faces major challenges related to the color persistence of products and the treatment of wastewater generated during processing. The discoloration of the dyes used, such as “Taicron Red”, is a major problem, as these dyes are chemically stable and difficult to remove. It is therefore essential to develop effective and sustainable methods for their treatment. The objective of this study was to evaluate the efficiency of a treatment system for the removal of textile dye “Taicron Red” in model solutions, using sustainable processes powered by solar energy. For this purpose, an electrolytic cell powered by a solar panel and a photoreactor whose pump is also driven by solar energy were designed and built. The treatment consisted of an electrocoagulation process with aluminum anodes, applying a potential difference of 12 volts for 40 min, which reduced the Chemical Oxygen Demand (COD) of the solution from 5216.7 ppm to an initial value that allowed a second electrocoagulation. Subsequently, the solution was treated in the photoreactor for 180 min using 100 mg of Fe(II), 12 ml/L of H₂O₂, pH = 3 and TiO₂ at 100 ppm, achieving a 60% COD removal (removing 3129.2 ppm) and 90.68% of the color. In a second treatment, increasing the concentration of TiO₂ to 1000 ppm, 84% COD removal (removing 4381.4 ppm) and 99.38% color removal were achieved. The results demonstrated that the proposed system is highly efficient for the removal of textile dye and COD, reaching high removal percentages in both cases, and that the use of solar energy in conjunction with electrocoagulation and photocatalysis processes is a viable and sustainable alternative for treating wastewater in the textile industry.